2010
DOI: 10.1002/etc.104
|View full text |Cite
|
Sign up to set email alerts
|

Sampling in the Great Lakes for pharmaceuticals, personal care products, and endocrine‐disrupting substances using the passive polar organic chemical integrative sampler

Abstract: The passive polar organic chemical integrative sampler in the pharmaceutical configuration (i.e., pharmaceutical-POCIS) was calibrated for sampling at water temperatures of 5, 15 and 25 degrees C to determine the influence of temperature on chemical-specific sampling rates (R(S)), thus providing more robust estimates of the time-weighted average concentrations of pharmaceuticals and personal care products (PPCPs) and endocrine-disrupting substances (EDS) in surface water. The effect of water temperature and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 200 publications
(177 citation statements)
references
References 33 publications
9
166
2
Order By: Relevance
“…The temperatures of the untreated wastewater at WWTP-S and WWTP-L were in this range over the sampling period, but temperatures of treated wastewater were in the range of 8-12°C. However, our previous studies have shown that sampling rates for POCIS do not vary widely with temperature, water flow, pH and dissolved organic content (Li et al, 2010a(Li et al, , 2010b(Li et al, , 2011. Overall, it appears that passive sampling using POCIS in complex matrices such as untreated wastewater would require different calibration approaches such as the in situ calibration suggested by Harman et al (2011) in order to obtain data on concentrations that can be reliably used to estimate community drug consumption.…”
Section: Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…The temperatures of the untreated wastewater at WWTP-S and WWTP-L were in this range over the sampling period, but temperatures of treated wastewater were in the range of 8-12°C. However, our previous studies have shown that sampling rates for POCIS do not vary widely with temperature, water flow, pH and dissolved organic content (Li et al, 2010a(Li et al, , 2010b(Li et al, , 2011. Overall, it appears that passive sampling using POCIS in complex matrices such as untreated wastewater would require different calibration approaches such as the in situ calibration suggested by Harman et al (2011) in order to obtain data on concentrations that can be reliably used to estimate community drug consumption.…”
Section: Compoundsmentioning
confidence: 99%
“…Procedures for this experiment were based on work previously reported by Macleod et al (2007), with some modifications reported by Li et al (2010a). Briefly, static experiments were conducted in triplicate in 4-L amber glass bottles situated in a temperature-controlled environmental chamber set to 20°C for a period of eight days.…”
Section: Pocis Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the sampling rates expressed as the volume of water (mL) cleared of silver 150 per day, static non-renewal experiments were conducted using procedures based on methods 151 described by Li et al, (2010) and MacLeod et al, (2007). In one set of experiments with the CNIS-152…”
Section: Sampling Rates 149mentioning
confidence: 99%